The Relationship Between Honey's Floral Origins and The Electrical Impedance of Honey Variants - Vivien Dwi Indriyani; Didik Rahadi Santoso; Chomsin Sulistya Widodo (Natural B, Journal of Health and Environmental Sciences, 2018)
One of the factors that influence the composition of honey is the plant that became the source of nectar. Honey derived from one plant species has a different composition with honey from other plant species. This study aims to analyze the effect of the origin of honey flower on the value of electrical impedance by using impedance spectroscopy and to analyze the relationship between ash content and electrical impedance in honey. This study used four gold needle electrodes and a set of PicoScope 5244B tools to measure the value of honey impedance. Measurements are made by injecting a current of 10 μA and using frequencies 1 Hz to 2 MHz. This study also measured ash content in honey. The sample used is kelengkeng, kaliandra, randu, coffee, and rubber honey. The results showed that the origin of honey flower affects the value of electrical impedance. The relationship between impedance and ash content is the smaller the ash content in honey the impedance value is greater.